The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1145/1113034.1113061
|View full text |Cite
|
Sign up to set email alerts
|

Who should govern the internet?

Abstract: Failing to share control, the U.S. risks driving disaffected countries to establish their own competing, independent root servers, thus creating parallel Internets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 2 publications
(3 reference statements)
0
1
0
Order By: Relevance
“…The initiative has been praised by numerous commentators, with one having suggested that 'its open multi-stakeholder nature can give it legitimacy, thus making it an important player in crystallising opinion on important issues'. 21 Its lack of teeth and regulatory claws appear however to be an inherent weakness of the initiative. As such, and in common with many other multi-lateral regulatory initiatives which are relatively toothless tigers in terms of sanctioning power, in order to gain regulatory traction and desirable levels of G. Gilligan and D. Bowman regulatory compliance, those who are regulated must ascribe sufficient levels of inherent legitimacy to the purposes and processes of relevant regulatory infrastructures.…”
Section: Introductionmentioning
confidence: 99%
“…The initiative has been praised by numerous commentators, with one having suggested that 'its open multi-stakeholder nature can give it legitimacy, thus making it an important player in crystallising opinion on important issues'. 21 Its lack of teeth and regulatory claws appear however to be an inherent weakness of the initiative. As such, and in common with many other multi-lateral regulatory initiatives which are relatively toothless tigers in terms of sanctioning power, in order to gain regulatory traction and desirable levels of G. Gilligan and D. Bowman regulatory compliance, those who are regulated must ascribe sufficient levels of inherent legitimacy to the purposes and processes of relevant regulatory infrastructures.…”
Section: Introductionmentioning
confidence: 99%